Effects of ABCB1 rs1045642 polymorphisms on the efficacy and safety of amlodipine therapy in Caucasian patients with stage I–II hypertension - Sychev D; Shikh N; Morozova T; Grishina E; Ryzhikova K; Malova E (Dove Medical Press, 2018)
Dmitry Sychev,1 Nadezhda Shikh,2 Tatiana Morozova,2 Elena Grishina,3 Kristina Ryzhikova,3 Elena Malova1 1Department of Clinical Pharmacology and Therapy, Russian Medical Academy of Continuous Professional Education, Ministry of Healthcare, Moscow, Russia; 2Department of Clinical Pharmacology and Pharmacotherapy, Institute of Professional Education, I.M. Sechenov First Moscow State Medical University, Ministry of Health of Russia, Moscow, Russia; 3Research Center, Russian Medical Academy of Continuous Professional Education, Ministry of Healthcare, Moscow, Russia Purpose: The aim of this study was to determine the impact of ABCB1 (MDR1) rs1045642 polymorphisms on the efficacy and safety of amlodipine in Caucasian patients. Patients and methods: The 12-week study included 100 patients. Patients with the newly diagnosed stage I–II hypertension (HT) were recruited to complete genotyping of the rs1045642 single-nucleotide polymorphism (SNP). The study design did not include a control group. Before treatment, all patients either did not undergo antihypertensive treatment at all or did not receive regular antihypertensive therapy. The initial dose was 5 mg/day. Four office blood pressure measurements, two 24-hour noninvasive ambulatory blood pressure measurements, and questionnaires of Tsvetov were used to evaluate the efficacy and safety of amlodipine. Results and conclusion: The highest antihypertensive effect in combination with the lowest incidence of adverse reactions was observed in the TT group, while patients with the CC genotype showed a low antihypertensive effect and the highest incidence of adverse effects. Patients with the CC genotype presented with adverse effects predominantly in the form of edema. A total of 33 patients reached the target blood pressure (SBP <140 mmHg; DBP <90 mmHg): two patients with the CC genotype (12%); 18 patients with the CT genotype (34%); and 13 patients with the TT genotype (43%). The intergroup differences were: CC vs CT, P=0.02; CC vs TT, P=0.02; and CT vs TT, P=0.05. The results of this study indicate the potential of pharmacogenetic testing for rs1045642 SNP when prescribing amlodipine for the first time in Caucasian patients with stage I–II arterial HT. Keywords: pharmacodynamics, rs1045642, personalized, side effects, CYP3A5, single-nucleotide polymorphism, SNP, P-glycoprotein